Characterization of Sago Starch Based Degradable Plastic with Calcium Carbonate (CaCO3) as Filler - Rozanna, Dewi; Novi Sylvia, B.; Zulnazri, C; Januar Parlaungan, Siregar D.; Medyan Riza, F. (INTI International University, 2023)
Research on finding substitute to plastic commercial has received massive attentions due to the environmental effect of plastic waste. Degradable plastic can be used as an alternate to synthetic plastic even though the properties especially mechanical characteristic. Sources of degradable plastic can be starch, cellulose, poly lactic acid, etc. Starch available in large quantities, cheap and renewable. The purpose of this study was to determine the effect of Calcium Carbonate (CaCO3) filler on characteristics of sago based degradable plastic. The degradable plastic properties analyzed were mechanical, chemical, thermal, water absorption and degradation rate. The preparation of degradable plastics was done in several stages, starting with the preparation of sago starch, synthesis of degradable plastic and characterization. Variations of CaCO3 composition and sorbitol plasticizer were used to observe their effect towards plastic properties. CaCO3 filler variations used were 2, 4, 6, 8% and sorbitol plasticizer variations were 25, 30, 35%. The highest tensile strength, Young's Modulus and elongation at break obtained were 6.24 MPa, 89.92 MPa and 154.80% respectively, at 0.8% calcium carbonate and 35% sorbitol. Fourier Transform Infra Red (FTIR) test results showed in thermoplastic starch from sago there were more free -OH hydroxyl groups due to the reduction of atoms that are hydrogen bonded. The absorption peaks in the range of wave numbers 2931.80 cm-1 indicated the presence of saturated aliphatic hydrocarbon chains (C-H), wave numbers of 1411.89 cm-1, 1334.74 cm-1, 1207.44 cm-1, 1149.57 cm-1, and 1078.81 cm-1 . It showed typical areas of C-O groups. Most of the compounds were hydrophilic which binds water, hence can be degraded by microbial activity in the soil. Thermal characterization using Differential Scanning Calorimetry (DSC) thermogram test indicated degraded plastic has a thermogram peak at 137.25°C. This peak indicates physical changes due to the loss of water groups content in plastic. The highest swelling value was 103.96 % obtained at 2% calcium carbonate and 35% sorbitol. The addition of CaCO3 filler improved the water resistance properties of degradable plastics. The degradation of sago starch-based plastics with CaCO3 filler was 16-24 days depending on the filler composition and has complied with ASTM D-20.96 (degradable plastics should decompose before 180 days)